Vilhena, colono ilustrado : a fronteira entre o literário e o histórico no estilo clássico português - Santos, Mayara Menezes (2018)
In Brazilian writing of the colonial era, the essay is traditionally defined by its historical, documental and descriptive nature and purpose; however, this type of text, consisting of ―narrative-letters‖ and ―chronicles‖, through which the reader is invited to comprehend the desires and hopes of some of the protagonists in the drama we call ―colonial life‖, also has an esthetic-literary dimension. The flexibility of this literary genre is rooted in the relationship between thought and word, and in the passage from experience to observation. Seen in these terms, this dissertation will analyze a text in which two intimately interconnected dimensions of knowledge – literature and history – can be readily identified, and which are deployed as a means of providing a better understanding of how established Portuguese narratives influenced the first literary productions in Brazil. The analysis focuses on the work of Luís dos Santos Vilhena, a Portuguese teacher of Greek living in Brazil, who cultivated the aesthetic norms established by Classical Antiquity, and whose testimony was published in a narrative entitled Recopilação de Notícias Soteropolitanas e Brasílicas (1802) (―A Compilation of News from Salvador and from Brazil‖). As an intellectual adherent of Enlightened Reformism (reformismo illustrado), Vilhena anticipated the crisis of the colonial system and, at the same time, provided a social, political and economic diagnosis of Brazil, on the basis of which he proposes to the Colony a series of reforms. In contrast, in his descriptions and his reporting of news from the ―captaincies‖ of Bahia, he alludes to the Classical world, evoking Roman and Greek myths, heroes and events, the names of poets and philosophers, and highlights their relations with both the celebrities and the common people of their time. Reflecting this duality, the dissertation begins by providing a dialogue between literature and history, in recognition of the fact that 18th century Enlightenment thought had established that, in the specific context under scrutiny, in order to comprehend the cultural history of the relations between metropolis and colony, the only literary material worthy of consideration consisted of resources drawn from the historical record. The publication and reception of Vilhena‘s manuscript is used to illustrate and test this characterization. Subsequently, we identify and evaluate the fictional elements that constitute ―enlightened discourse‖, above all the coexistence of the production of meaning and the metaphorical mechanism that together reflect the hybrid character of the essay genre. The historical-literary analysis, based on the methodology adopted by Antônio Candido (2005), using the first edition of Braz de Amaral (1921), examines allegorical schemes with a view to recuperating and re-evaluating the role of the fictionality of ―narrative-letters‖ in the constitution of Brazilian literature. These works, by adorning discourse in a literal-figurative manner, reveal the meaning of the things, the men and the real events of that time, and allow us to perceive how values and feelings are reflected in literary works.